Parasite diversity at the Holarctic nexus: species of Arostrilepis (Eucestoda: Hymenolepididae) in voles and lemmings (Cricetidae: Arvicolinae) from greater Beringia - Makarikov, Arseny A.; Galbreath, Kurt E.; Hoberg, Eric P. (Zootaxa, 2013)
Previously unrecognized species of hymenolepidid cestodes attributable to Arostrilepis Mas-Coma & Tenora, 1997 in arvicoline rodents from the greater Beringian region and western North America are described. Discovery and characterization of these tapeworms contributes to the recognition of a complex of cryptic species distributed across the Holarctic region. Three species are proposed: Arostrilepis gulyaevi sp. n. is named for cestodes in Myodes rufocanus from the Republic of Buryatia, southeastern Siberia and from the Khabarovskiy Kray, Chukotka Autonomous Okrug, and Magadanskaya Oblast’, Russian Far East (western Beringia); A. cooki sp. n. is named for cestodes in Myodes gapperi from British Columbia, Canada and Montana, USA; and A. rauschorum sp. n. is named for cestodes in Microtus oeconomus, M. longicaudus, M. pennsylvanicus and M. xanthognathus from the Brooks Range, Seward Peninsula, north-central interior, and Arctic coastal plains of Alaska (eastern Beringia) and Montana, USA. Consistent with recent studies defining diversity in the genus, the form, size, and spination (pattern, shape and size) of the cirrus are diagnostic; species are further distinguished by the relative position and length of the cirrus sac, and arrangement of the testes. Assessment of genetic data from the cytochrome b gene of mitochondrial DNA complements differentiation of this complex based on morphological attributes and confirms known species diversity within the genus. New data for geographical distribution and host specificity of known Arostrilepis spp. indicate that 3 of 12 recognized species have Holarctic distributions extending across Beringia. These include Arostrilepis beringiensis (Kontrimavichus & Smirnova, 1991) in lemmings (species of Lemmus and Synaptomys), A. cf. janickii Makarikov & Kontrimavichus, 2011 in root voles (M. oeconomus) MAKARIKOV ET AL. 402 · Zootaxa 3608 (6) © 2013 Magnolia Press and A. macrocirrosa Makarikov, Gulyaev & Kontrimavichus, 2011 in red backed voles (species of Myodes) and less often other rodent host species.